Evaluation of the Amplicor Chlamydia trachomatis test versus culture in genital samples in various prevalence populations. Issue 3 (June 1994) - de Barbeyrac, B; Pellet, I; Dutilh, B; Bébéar, C; Dumon, B; Géniaux, M; Bébéar, C
Abstract : OBJECTIVE--To evaluate a newly developed polymerase chain reaction (PCR) assay, Amplicor C trachomatis for the detection of C trachomatis in genital samples using cell culture for comparison. SUBJECTS--501 patients (431 women and 70 men) attending an STD clinic in Hôpital Pellegrin (high-risk population) and gynaecological clinics (low-risk population) in Bordeaux, France. METHODS--The genital samples (cervical and urethral) were tested for the presence of C trachomatis using the Amplicor test and using standard cell culture identified by the immunofluorescence test using a monoclonal antibody to C trachomatis. Discrepancies between the results of culture and Amplicor were further analysed by major outer membrane protein gene (omp1)-PCR of the specimens taken in transport media and by direct fluorescent antibody (DFA) staining of elementary bodies in culture transport tubes. RESULTS--After analysis of discrepancies, the revised sensitivity and specificity of PCR were 95.3% and 100% and the positive and negative predictive values were 100% and 99.5%, respectively. CONCLUSION--The present results indicate that the Amplicor assay is rapid, specific and more sensitive than the culture method. This test provides an excellent non-culture method for the detection of C trachomatis in various prevalence populations.